Understand the Perception of the General Public towards Stock Market: Exploring the factors influencing public perception of the stock market (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The globalization of financial markets has been raising the dimensions of the town of list investors' over the past 2 years by giving a multitude of the market as well as investment choices. Hence, it will make the investment choices of their process more complicated. The elements influencing investor's perception are actually returning on risk, market trend, or investment, short term profitability, cost of the share, dividend policy, past economic performance, company reputation, the standing of the board, present earnings of the business as well as an expert opinion. A quantitative strategy continues to be utilized by ascertaining variables and utilizing statistical methods to recognize the perception of the general public. The foundation has been supplied for future investigation depending on the important principles of the study.